Pathogenic germline variants in patients with breast cancer: conversations across generations, practices and patients’ attitude - Abdel-Razeq, Hikmat; Mustafa, Rawan; Abdel-Razeq, Sarah; Abu-Fares, Hala; Al Masri, Sama; Damsees, Rana; El-Atrash, Mariam; Elemian, Shatha; Alkyam, Mais; Ammar, Khawlah; Bater, Rayan; Kderat, Marah; et al. (Frontiers in Genetics, 2023)
Background: Breast cancer susceptibility genes such as BRCA1, BRCA2, PALB2, CHEK2 and many others are increasingly recognized among our patient population. In addition to their impact on treatment decisions of tested patients themselves, identifying at-risk family members offer opportunities for cancer preventive measures.Methods: This is an observational cross-sectional study of adult breast cancer patients with positive breast-cancer-susceptibility germline variants who received treatment at our institution. Patients with variants of uncertain significance (VUS), or who refused to give consent, were excluded. The data was collected from an eligible sample of breast cancer patients using a structured questionnaire developed by the study team and tested for validity and reliability, as well as a clinical chart review form. Patients were invited to participate in the study during their scheduled oncology clinics visit.Results: 169 patients were enrolled, including 42 (24.9%) with pathogenic/likely pathogenic (P/LP) BRCA1 variants, 84 (49.7%) with BRCA2 and 43 (25.4%) with non-BRCA variants. All patients were female and the mean age was 45±9.9 years. Among 140 eligible patients, 104 (74.3%) underwent prophylactic mastectomy, while 79 (59.0%) of 134 eligible patients had prophylactic bilateral salpingo-oophorectomy (BSO). Results were communicated with family members by majority (n=160, 94.7%), including 642 first degree female relatives, and 286 (44.5%) of them have taken no action. Fear of positive test results, cost of testing, unwillingness to undergo preventive measures, and social stigma were cited as barriers to genetic testing in 54%, 50%, 34% and 15%, respectively.Conclusions: Risk-reducing interventions including mastectomy and BSO were carried by majority of patients with P/LP variants. However, though the rate of communication of genetic testing results with family members was high, proper preventive measures were relatively low. Cost and fear of cancer diagnosis, were the leading causes that prevented cascade testing in our cohort.